The Ownership Concept in Modern Management – How to Become More Efficient (Outsourcing Viewpoint) - Flieger, Michał (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to present the ownership concept in modern management in the scope of the outsourcing viewpoint. The author analyse the exreengineering concept of the outsourcing in management – the process configuration that may result in cost savings and greater flexibility of production or other internal processes.